KEGIATAN PENGEMBANGAN KREATIVITAS ANAK USIA 5-6 TAHUN DI TK PRIMANDA UNTAN (Studi kasus pembelajaran pada saat pandemi covid-19) - Fransiska Tiara; Muhamad Ali; Lukmanulhakim Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to examine the creativity development activities of children aged 5-6 years during the covid-19 pandemic. The research method used is qualitative in the form of case study research, because this research was carried out at a certain time, namely during the covid-19 pandemic. Data collection tools through observation sheets, interview guidelines and documentation with data sources 2 teachers. The general problem in this study is how to develop the creativity of children aged 5-6 years in Primanda Untan Kindergarten (a case study of learning during the covid-19 pandemic). The results showed (1) Learning activities at Primanda Untan Kindergarten during the COVID-19 pandemic were still carried out by referring to the Regulation of the Minister of Health of the Republic of Indonesia Number 9 of 2020 concerning Guidelines for Large-Scale Social Restrictions in the Context of Accelerating Handling of Corona Virus Disease 2019 (Covid-19). ). currently applicable (3) The learning media used by teachers to develop the creativity of children aged 5-6 years at Primanda Untan Kindergarten during the covid-19 pandemic are media for drawing, coloring and making works of art 4) The learning methods used by teachers to develop children's creativity ages 5-6 years in Primanda Untan Kindergarten at the time of the covid-19 pandemic is men use the assignment method.Keywords: Creativity Development, Teachers, Covid-19 Pandemic